Preventive security measures as punitive applications of the Mexican State to the dangerous subject of a criminal charge - Vázquez Pérez, Eduardo Daniel (2023)
The purpose of this paper is to demonstrate that the Mexican State has regulatory mechanisms for the isolation of potentially dangerous individuals. By this I mean that the measures implemented in terms of prevention and security adopted by the Mexican State in 2008 are permeated by the criminal law of the enemy, whose primary objective is to safeguard the integrity and security of persons in a context characterized internationally by high levels of violence. In this sense, these preventive mechanisms, which are telematic control, security custody and probation, serve as precautionary measures and continuity of the penalty to the offender of the legal rule, since they seek to exclude from society that non-communication (non-person), as a result of noncompliance with the socially assigned role that communicationally and functionally harms the dynamism of the social system, since this malicious act of the non-person can put it at risk or, if necessary, destabilize it.